Compliance to albendazole therapy under national deworming day programme at schools in Goa: a questionnaire survey - Dhupdale, Nitin Y.; Cacodcar, Jagdish A.; Giri, Purushottam A.; S., Vijay; Naik, Akshaya (International Journal Of Community Medicine And Public Health, 2017)
Background: Ministry of Health and Family Welfare, Government of India observed National Deworming Day (NDD) on February 10, 2016 and second round on August 10, 2016 in all 36 States/UTs of the country. The same initiative was implemented in the state of Goa; the present study was aimed at evaluating this initiative. The objectives of the study were to find the compliance of school children to albendazole tablets and also to find any side effects encountered by the students. Methods: A cross-sectional study was conducted in month of Ocober 2016 amongst total of 266 parents completed a self-administered questionnaire. The Data retrieved from completed questionnaires was entered in EpiDATA and analysed by SPSS version 23. Results: Of the total 65.8% of students received albendazole tablets. The overall compliance to the albendazole was 61.3%. Only 4.1% of students developed minor adverse reactions. Overall 78.9% of the parents were willing to participate in the next round of NDD. Conclusions: The compliance to the albendazole was less than expected. There is a greater need to involve parents and teachers to improve the compliance of students towards albendazole to achieve desired outcomes.